KAJIAN PROFIL LEKOSIT PADA KUCING PERSIA DAN KUCING DOMESTIK DI RUMAH SAKIT HEWAN PROF. SOEPARWI YOGYAKARTA - , EKA SAFAR OKTAFIANO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cats become one of the the most popular animal. Persian cats are usually maintained specifically with different maintenance to domestic cats. Domestic cats were also attracted by many Indonesian people. Health status and process of a disease can be seen from examination of leucocytes. Leukocytes have a major role in cellular and humoral defense. Total of leukocytes that deviate from the normal state has an important clinical meaning. Differences in the number of leukocytes in each individual influenced by several factors such as stress, physiological activities, age and others. The purpose of this study was done to see the leukocytes profile between Persian cat and Domestic cat. This study used 35 healthy cats including 18 Persian and 17 Domestic cats. Blood tests were conducted on the calculation of the total leukocytes, neutrophils, lymphocytes, and monocytes. Leukocyte counts is done by using a Benjamin (1978) Method. Observations were made using a microscope, the number of cells counted in four large boxes multiplied by 50. Calculating the value of neutrophils, lymphocytes and monocytes performed on smear preparations using a microscope with a magnification of 10 Ã 100, and 100 cells counted number of leukocytes. Value obtained is the percentage (relative value) of each type of leukocyte. The absolute value obtained by multiplying the percentage of each type of leukocytes to the total number of leukocytes. Blood tests carried out on Prof Soeparwi Animal Hospital. Data obtained calculated average and standard deviation, then the data analyzed descriptively. The results showed that leukocytes on Persian and Domestic cat research were still in the normal range of leukocytes data of Jain (1993) and there are no significant differences (P> 0.05). Keywords : Cat, persian, domestic, blood, leukocytes